Financial analysis of a locomotor exercise trial for post-stroke recovery: insights from the HIT Stroke Trial - Hazen, Emily M.; Bartsch, Bria L.; Billinger, Sandra A. (Frontiers in Stroke, 2024)
Background: Navigating the complexities of post-stroke recovery trials requires addressing challenges in participant recruitment and retention and effective resource management to ensure trial success. The aim of this study was to examine the financial requirements associated with conducting the Moderate-Intensity Exercise Versus High-Intensity Interval Training to Recover Walking Post-Stroke (HIT Stroke Trial) at a single site encompassing a wide catchment area, recognizing the intricate challenges of participant recruitment and retention inherent in post-stroke recovery trials. Methods: To determine cost, study expense reports were gathered and divided into seven categories: recruitment, screening assessments, baseline assessments, intervention, outcome assessments, retention, and oversight. Categories were then further divided into chronological order for initial contact and prescreening, consenting, initial screening, and baseline testing. The 12-week intervention was divided into 4-week blocks: intervention block 1, post 4-week outcome testing, intervention block 2, post 8-week outcome testing, intervention block 3, and post 12-week outcome testing. Results: Total direct cost for site execution was 539,768 with cost per participant approximated as 35,984. Oversight costs accounted for 65.8% of the budget at 355,661. To achieve goals related to inclusive participant recruitment (21,923) and retention (28,009), our site costs totaled 49,932. Direct study-related costs included screening assessments (5,905), baseline assessments (15,028), intervention (76,952), and outcome assessments (36,288). Discussion: Clinical trials focusing on walking rehabilitation and exercise, particularly those requiring multiple assessment visits, demand rigorous oversight. This cost analysis provides important and critical insight into the expenses required to successfully execute an exercise-based walking rehabilitation trial in the United States.